PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN DAN PROMOSI CASHBACK TERHADAP MINAT MAHASISWA DALAM MENGGUNAKAN DOMPET DIGITAL SHOPEEPAY PADA APLIKASI SHOPEE - Fitri Mawardani; Renny Dwijayanti (Jurnal Pendidikan Tata Niaga (JPTN), 2021)
The number of Financial Technology (fintech) users has been increasing every year in Indonesia. For the past years, the most used Financial technology (fintech) is ShopeePay digital wallet. Convenience and promotion are the consumer attractions that influence their interest in using a system. A system’s convenience is based on trust. The purpose of this study was to determine the effect of convenience and cashback promotion perceptions on students’ interest in using the ShoopePay digital wallet. This type of research uses descriptive quantitative with a population of 1082 students in the Department of Economics Education class 2017-2020. Sampling using purposive sampling technique. The number of samples used 92 respondents by distributing online questionnaires in the form of google forms. Data processing using multiple linear regression with SPSS 22 apllication. The results of this study indicate that perceived ease of use and cashback promotion have a simultaneous effect on students’ interest in using the ShoopePay. Hopefully, this research becomes a reference for future researchers and digital economics entrepreneurs in the marketing field. Keywords : Perceived ease of use;Cashback Promotion; Interest in Use.